Transparent thin film transistors by solution process - Chong, How Han. (2010)
Thin film transistor (TFT) technologies have been the great force behind the development of display for the past few decades. In today’s display industry, TFT is still the backbone for Active Matrix Liquid Crystal Display (AMLCD) and Active Matrix Organic Light Emitting Diode (AMOLED). While silicon based TFT is dominating the market, it possesses limitations, such as instability of threshold voltage and electron mobility. Furthermore, the fabrication cost of TFT with conventional methods is still very high, which make the price of displays a concern. Solution processed TFT is aimed to reduce the complexity and fabrication cost by means of simple and low cost methods. Moreover, materials with wide bandgap (transparent) and high mobility, such as zinc oxide were proved to be stable and can be processed at ambient conditions. Compare to silicon based material, zinc oxide based material has many advantages that are suitable for TFT. Thus, it possesses a great potential as an alternative to amorphous silicon as the active layer material in TFT. In this project, two solution processing methods will be discussed – spray pyrolysis and ink-jet printing. These methods are chosen for this project because they are simple, economical and use less chemical during fabrication. Therefore, it is worth to explore the feasibility to fabricate TFT using these two methods. Besides, pure zinc oxide (ZnO), indium zinc oxide (IZO) and indium gallium zinc oxide (IGZO) are used in the experiments to study the effect of indium and gallium in zinc oxide thin film and hence the device performance. Bottom gate top contact TFTs were fabricated using spray pyrolysis method and bottom gate bottom contact TFTs were fabricated using ink-jet printing method.